PENTINGNYA REGULASI KHUSUS SISTEM FACE RECOGNITION TECHNOLOGY SEBAGAI PRODUK ARTIFICIAL INTELLIGENCE DALAM PENINGKATAN KEAMANAN DAN PENEGAKAN HUKUM DI INDONESIA - Br Girsang, Sarimah Yemima (Magister Hukum Universitas HKBP Nommensen, 2024)
Seeing the large number of misuses of personal data through Face Recognition Technology, it is necessary to protect every personal information. So far, Indonesia already has a Personal Data Protection Law. This regulation is considered insufficient to provide protection for the use of facial recognition. This research aims to determine the development of legal regulations for the use of FRT as well as the government's efforts to increase personal data protection. This research uses a normative juridical approach method with analytical descriptive writing specifications. The research results show that Indonesia does not yet have specific regulations governing the use of facial recognition. The regulations are included in the Personal Data Protection Law so further regulations are needed to provide regulatory specifications for the use of FRT technology.